Going Platinum: The European Journal of Soil Science at 75 - Dungait, Jennifer A. J.; Evans, Daniel L.; Farrell, Mark; He, Hailong; Heuvelink, Gerard B. M.; Schmidt, Olaf (Wiley, 2024)
The European Journal of Soil Science (EJSS) is published by Wiley on behalf of the British Society of Soil Science (BSSS) to fulfil its original mission to ‘publish an annual publication’. The Journal for Soil Science published its first issue in March 1949 (Figure 1, left) before a change of name to the European Journal of Soil Science (EJSS) in 1994. The current issue (Volume 75, Issue 2, March-April 2024; Figure 1, right) therefore marks our 75th Anniversary. In this Editorial, we (the Senior Editorial Team of the EJSS; Figure 2) review briefly how the journal has evolved over the last three-quarters of a century and look forward to both the challenges and opportunities that the future holds.